Summertime aerosol chemical components in the marine boundary layer of the Arctic Ocean - Xie, Zhouqing; Sun, Liguang; Blum, Joel D; Huang, Yuying; He, Wei (Journal of Geophysical Research: Atmospheres, 2006)
Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/95013/1/jgrd12367.pdf